Impact stories and testimonies from diverse actors in groundnut value chain in Tanzania - Akpo, E.; Ojiewo, Christopher Ochieng; Omoigui, L.O.; Rubyogo, Jean-Claude; Varshney, Rajeev K. (Springer, 2020)
Adamu, a groundnut farmer from Maugura village, Masasi, shared his success story for being involved in TL projects . “I was taught how to grow the seeds, carry out diagnosis, how to store them, among other things. This year, there are some seeds that I have begun putting on the ground so that I can continue conducting research about them. Naliendele Institute gave me about 20 lines and I am working on all of them. In fact, they have not yet been named. I’ve just planted them in plots; from plot number one to plot number twenty.”